Needs assessment Phase II Collecting data - Altschuld, James W. (Los Angeles, [California] London SAGE, 2010)
This text covers the five most common instruments and strategies employed to explore needs. It describes the steps involved in implementing them and presents case illustrations
Title from title screen (viewed October 20, 2023)
Includes bibliographical references and index
Specialized
Description based on print version record
Keywords: Needs assessment; Strategic planning